100 things every designer needs to know about people - Weinschenk, Susan, ....- ([S.l.] : Peachpit Press, 2020)
We design to elicit responses from people. We want them to buy something, read more, or take action of some kind. Designing without understanding what makes people act the way they do is like exploring a new city without a map: results will be haphazard, confusing, and inefficient. This book combines real science and research with practical examples to deliver a guide every designer needs. With this book you'll design more intuitive and engaging apps, software, websites and products that match the way people think, decide and behave.
Keywords: Consumentengedrag; Design thinking